Decentralization of Public Authorities in Ukraine: Theoretical-Legal and Administrative Aspects - Terletskii, Anatoliy; Andreiev, Dmytro; Kachan, Vasyl; Leshchenko, Oleksandr; Mashchenko, Olha (Jurnal Cita Hukum, 2024)
The research aims to reveal the administrative-legal, environmental, social and customs principles of decentralising public authority in Ukraine. Main content. The article reveals the main definitions of decentralisation of power and analyses the advantages and disadvantages of decentralisation in the public administration system. The article also presents the basic typology of decentralising power in foreign countries. It characterises these types, as well as an attempt to summarise the reasons for performing decentralisation in Ukraine.  Methodology:  The use of systemic, functional, and structural methods in this study made it possible to define concepts and types, as well as to establish the reasons for the introduction of the decentralisation reform in Ukraine. Conclusions. Various approaches to reform in European countries and their results have been considered due to the need to implement decentralisation in Ukraine. The result of the work consists of determining the main definitions of the decentralisation of power, analysis of the advantages and disadvantages of the decentralisation process, definition of the main types of decentralisation, and generalisation of the main reasons for introducing decentralisation in Ukraine.